Apostasy: a legal implication on Malay reservation land’s ownership / Rusnadewi Abdul Rashid - Abdul Rashid, Rusnadewi (2015)
Apostasy in Islam is commonly defined as the rejection in word or deed of one's former religion by a person who was previously a follower of Islam. This article aims to examine the effect of ownership of an apostate toward Malay Reservation Land’s title, which can only be owned and dealt over by Malays or persons deemed native residents of the state. This relates to the issue as to whether an apostate is still considered as ‘Malay’ since religion is an essential element of Malay ethnic identity. Under Article 160 (2) of the Federal Constitution and all thirteen States of Malay Reservation Enactments in Malaysia, the use of the term ‘Malay’ refers to a person professing Islam. If this interpretation is to be applied strictly, a Malay citizen who converts out of Islam may no longer considered ‘Malay’ under the law and hence denied the privilege afforded to Malays under the Article 89. The result from the literature reviews shows that the previous discussion construed Islam as an identity of Malay. However, there is no study carried out to suggest that apostasy become a ground for forfeiture of Malay Reservation Land title. This article is based on a qualitative study and the approach applied is a content analysis methodology. This paper will attempt to delve into the definition of Malay and the effect of apostasy towards the ownership of Malay Reservation Land. It is expected that the paper will provide the answer regarding the ownership of Malay Reservation Land title in Malaysia held by an apostate.